Arterial ligation in anterior resection for rectal cancer: A validation study of the Swedish Colorectal Cancer Registry. (July 2014) - Boström, Petrus; Rutegård, Jörgen; Haapamäki, Markku; Matthiessen, Peter; Rutegård, Martin
ABSTRACT Background. The level of arterial ligation has been a variable of the Swedish Colorectal Cancer Registry since 2007. The aim of this study is to evaluate the accuracy of this registry variable in relation to anterior resection for rectal cancer. Methods. The operative charts of all cardiovascularly compromised patients who underwent anterior resection during the period 2007–2010 in Sweden were retrieved and compared to the registry. We selected the study population to reflect the common assumption that these patients would be more sensitive to a compromised visceral blood flow. Levels of vascular ligation were defined, both oncologically and functionally, and their sensitivity, specificity, positive and negative predictive values, level of agreement and Cohen's kappa were calculated. Results. Some 744 (94.5%) patients were eligible for analysis. Functional high tie level showed a sensitivity of 80.2% and a specificity of 90.1%. Positive and negative predictive values were 87.7 and 83.8%, respectively. Level of agreement was 85.5% and Cohen's kappa 0.70. The corresponding calculations for oncologic tie level yielded similar results. Conclusion. The suboptimal validity of the Swedish Colorectal Cancer Registry regarding the level of vascular ligation might be problematic. For analyses with rare positive outcomes, such bowel ischaemia, or with minor expected differences in outcomes, it would be beneficial to collect data directly from the operative charts of the medical records in order to increase the chance of identifying clinically relevant differences.